Short-term results of switchback from aflibercept to ranibizumab in neovascular age-related macular degeneration in clinical practice - Despreaux, Raphaelle; Cohen, Salomon Y.; Semoun, Oudy; Zambrowski, Olivia; Jung, Camille; Oubraham, Hassiba; Souied, Eric H. (Graefe's archive for clinical and experimental ophthalmology, 2016)
Purpose This work was undertaken to analyze the efficacy of switchback from aflibercept to ranibizumab in patients with neovascular age-related macular degeneration (nAMD) who had previously switched from ranibizumab to aflibercept. Methods This retrospective double-center study included 45 patients with nAMD who were previously treated with ranibizumab, then aflibercept, and then ranibizumab again, regardless of the number of intravitreal injections received. The primary outcome was change in best-corrected visual acuity (BCVA) measured on the Early Treatment Diabetic Retinopathy Study ETDRS chart before (T0) and after (T1) the switch, and 3 months after the switchback (T2). Secondary outcomes included changes in central foveal thickness (CFT) measured at T0, T1, and T2, as analyzed on spectral-domain optical coherence tomography (SD-OCT), and the percentage of patients gaining five letters or better. Results Forty-seven eyes of 45 patients were switched back from aflibercept to ranibizumab. The mean BCVA was 67.4 ± 13.4 at T0, 66.7 ± 14.4 at T1, and 68.2 ± 13.9 at T2. BCVA was significantly improved between T1 and T2 ( p = 0.0230), but not between T0 and T1 ( p = 0.5153) or between T0 and T2 ( p = 0.4248). The mean CFT decreased from 317.8 μm ± 89.6 at T0 to 306.9 μm ±68.0 at T1, and to 291.2 μm ± 76.6 at T2. The decrease in CFT was not statistically significant between either T0 and T1 or T1 and T2, but was significant between T0 and T2, when compared before switch and after switchback ( p = 0.0027). However, when considering eyes that received three or more consecutive intravitreal injections of aflibercept before switchback, the statistical significance between T1 and T2 was lost, although a trend towards significance remained ( p = 0.06). Thirteen eyes (27.7 %) gained five letters or more (range, 5–15 letters) after switchback. Conclusions A short-term benefit of switchback from one anti-VEGF agent to another was observed in patients with nAMD who had shown no benefit from the initial switch.